Palliative care in the emergency department: A systematic literature qualitative review and thematic synthesis. (October 2018) - Cooper, Esther; Hutchinson, Ann; Sheikh, Zain; Taylor, Paul; Townend, Will; Johnson, Miriam J
Background: Despite a fast-paced environment, the emergency clinician has a duty to meet the palliative patient's needs. Despite suggested models and interventions, this remains challenging in practice. Aim: To raise awareness of these challenges by exploring the experience of palliative care patients and their families and informal carers attending the emergency department, and of the clinicians caring for them. Design: Qualitative systematic literature review and thematic synthesis. Search terms related to the population (palliative care patients, family carers, clinicians), exposure (the emergency department) and outcome (experience). The search was international but restricted to English and used a qualitative filter. Title, abstracts and, where retrieved, full texts were reviewed independently by two reviewers against predefined inclusion criteria arbitrated by a third reviewer. Studies were appraised for quality but not excluded on that basis. Data sources: MEDLINE [1946-], Embase[1947-], CINAHL [1981-] and PsycINFO [1987-] with a bibliography search. Results: 19 papers of 16 studies were included from Australia ( n = 5), the United Kingdom ( n = 5), and United States ( n = 9) representing 482 clinical staff involved in the emergency department (doctors, nurses, paramedics, social workers, technicians), 61 patients and 36 carers. Nine descriptive themes formed three analytic themes: 'Environment and Purpose', 'Systems of Care and Interdisciplinary Working' and 'Education and Training'. Conclusion: In the included studies, provision of emergency palliative care is a necessary purpose of the emergency department. Failure to recognise this, gain the necessary skills or change to systems better suited to its delivery perpetuates poor implementation of palliative care in this environment.